A new taxonomy was developed for overlap across 'overviews of systematic reviews': A meta‐research study of research waste. (23rd January 2022) - Lunny, Carole; Reid, Emma K.; Neelakant, Trish; Chen, Alyssa; Zhang, Jia He; Shinger, Gavindeep; Stevens, Adrienne; Tasnim, Sara; Sadeghipouya, Shadi; Adams, Stephen; Zheng, Yi Wen; Lin, Lester; et al.
Abstract: Multiple 'overviews of reviews' conducted on the same topic ("overlapping overviews") represent a waste of research resources and can confuse clinicians making decisions amongst competing treatments. We aimed to assess the frequency and characteristics of overlapping overviews. MEDLINE, Epistemonikos and Cochrane Database of Systematic Reviews were searched for overviews that: synthesized reviews of health interventions and conducted systematic searches. Overlap was defined as: duplication of PICO eligibility criteria, and not reported as an update nor a replication. We categorized overview topics according to 22 WHO ICD‐10 medical classifications, overviews as broad or narrow in scope, and overlap as identical, nearly identical, partial, or subsumed. Subsummation was defined as when broad overviews subsumed the populations, interventions and at least one outcome of another overview. Of 541 overviews included, 169 (31%) overlapped across similar PICO, fell within 13 WHO ICD‐10 medical classifications, and 62 topics. 148/169 (88%) overlapping overviews were broad in scope. Fifteen overviews were classified as having nearly identical overlap (9%); 123 partial overlap (73%), and 31 subsumed (18%) others. One third of overviews overlapped in content and a majority covered broad topic areas. A multiplicity of overviews on the same topic adds to the ongoing waste of research resources, time, and effort across medical disciplines. Authors of overviews can use this study and the sample of overviews to identify gaps in the evidence for future analysis, and topics that are already studied, which do not need to be duplicated.